Investigating the Synergistic Relationship between Enterprise Resource Planning and Business Intelligence - Ansari, Nazeen; Thampi, Gopakumaran (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
This study aims to discuss the synergistic relationship between enterprise resource planning (ERP) and business intelligence (BI). It focuses on the benefits obtained from ERP and BI framework integration. The purpose of this study is to identify the software engineering challenges associated with ERP–BI integration. It also discusses methods for ERP–BI integration and shift toward open source and standard-based integration technologies.